2020
DOI: 10.24042/ajpm.v11i2.6903
|View full text |Cite
|
Sign up to set email alerts
|

Discovery Learning with Scaffolding To Promote Mathematical Creative Thinking Ability And Self-Efficacy

Abstract: Mathematical creative thinking ability and self-efficacy are a combination of abilities students need to have when studying mathematics. Mathematical learning is expected to improve both abilities. However, teachers still use conventional learning such as direct teaching, which results in a low increase in students' mathematical creative thinking abilities and self-efficacy. So we need alternative student-centred learning and teachers as facilitators who provide scaffolding. The study was conducted to obtain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 58 publications
0
5
0
3
Order By: Relevance
“…Multimedia can facilitate students in learning mathematical objects which are marked by the development of mathematical creative thinking skills [51,52]. Abstract mathematical objects such as geometry can be visualized with multimedia, making it easier for the students to understand the learning materials [53][54][55]. In addition, the animation provided can help students to construct the geometry concepts being learned.…”
Section: E Evaluation Stagementioning
confidence: 99%
“…Multimedia can facilitate students in learning mathematical objects which are marked by the development of mathematical creative thinking skills [51,52]. Abstract mathematical objects such as geometry can be visualized with multimedia, making it easier for the students to understand the learning materials [53][54][55]. In addition, the animation provided can help students to construct the geometry concepts being learned.…”
Section: E Evaluation Stagementioning
confidence: 99%
“…Menurut Rasnawati et al (2019) pemahaman berada pada tingkat yang lebih rendah daripada berpikir kreatif. Menurut Jatisunda et al (2020) "It is necessary to innovate the learning process in order to increase creativity". Artinya perlu adanya inovasi dalam proses pembelajaran guna meningkatkan kreativitas.…”
Section: Pendahuluanunclassified
“…Additionally, and Rahayuningsih et al (2022) suggested that students with high self-efficacy are likelier to possess high mathematical creative thinking ability and vice versa. Furthermore, Jatisunda et al (2020) highlighted that the higher the mathematical creative thinking ability, the higher the self-efficacy, and vice versa.…”
Section: She Additionally Reported Increased Students' Mathematical C...mentioning
confidence: 99%